ENVIROMENTAL GOVERNANCE, LOCAL WISDOM, AND FINANCIAL SUSTAINABILITY: EMPOWERING WOMEN ENTREPENUEURS IN SOUTH SUMATERA - Andriana, Isni; Ahmad Maulana, Ahmad Maulana; Badia Perizade, Badia Perizade; Umi Kalsum, Umi Kalsum; Thamrin, Kemas; Rifanka, Namira (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
Indonesia's economic growth has been significantly driven by women entrepreneurs in SMEs, which are vital for job creation and income generation. However, these enterprises face challenges in scaling and sustainability, influenced by social, environmental, economic, and governance factors. This study explores the mediating role of local wisdom in village environmental governance for the financial sustainability of women-led SMEs in South Sumatera, using the Triple Bottom Line (TBL) framework. A survey-based approach collected data from women entrepreneurs in formal and informal sectors, analyzed using Partial Least Squares (PLS) with Smart-PLS software. Findings reveal that local wisdom positively impacts financial sustainability through environmental governance, reinforcing the TBL’s emphasis on economic, social, and environmental balance. The study underscores the role of women entrepreneurs in fostering sustainable business practices and contributes to green entrepreneurship literature, calling for further research on sustainability-driven entrepreneurship in Indonesia.